Movimentos decoloniais no estágio de língua inglesa: sentidos outros coconstruídos nas vivências em uma escola pública - Silva, Valéria Rosa da (2021)
This research is an escrevivência (EVARISTO, 2020), that is, a writing-living experience, and derives from my concern over the status quo of practicum in teacher education programs, especially with regard to the distancing between university and basic education. The focus of this study is on an English language practicum experience in a B.A. in Portuguese and English teaching, at a public university in the countryside of Goiás, which occurred in 2017, and on events that took place in a public school. My main objective is to discuss decolonial movements that we sought to build by questioning the meanings of this experience constructed by its research agents as well as the tensions and conflicts inherent in this process. Decolonial movements, in this escrevivência far from being seen as revolutionary and redemptive, are localized and contingent attitudes, which attempt to unveil, problematize, and confront colonialities (QUIJANO, 2005). The epistemological basis of this work on critical teacher education and language education in the English language practicum were built from praxiologies enacted by its agents – seven female and three male student teachers, an English schoolteacher, and I, as university practicum professor. Hence, the empirical material, generated from different sources – dialogue circles, initial and final reflections on the practicum experience, notes on school life events, final reflections on the project, experience reports, and narratives – is not understood as data to be analyzed, but knowledge. From a proposal for an ecology of knowledges (SOUSA SANTOS, 2010, 2019), I seek to intertwine the agents’ knowledge of this escrevivência with others’ knowledge that, in some way, is related to this proposal, which lies within the broad scope of critical applied linguistics (BORELLI, 2018; JORDÃO, 2013; MASTRELLA-DE-ANDRADE, 2018; MATEUS, 2013; MOITA LOPES, 2006; MONTE MÓR, 2013a; PENNYCOOK, 2001, 2006; PESSOA, 2014; SILVESTRE, 2017). In addition, as I paid heed to the need to expand this field of research by disrupting disciplinary boundaries, I was inspired by studies from other fields of knowledge that resonate with southernized and decolonial epistemologies (ARÍAS, 2011; CASTRO-GÓMEZ, 2007; EVARISTO, 2020; FREIRE, 2005, 2013; KILOMBA, 2019; KRENAK, 2019a; MENEZES DE SOUZA, 2019a, 2020; MUNDURUKU, 2017a; QUIJANO, 2005; REZENDE, 2018; SOUSA SANTOS, 2019; WALSH; MIGNOLO, 2018). I use southernized and decolonial epistemologies as umbrella terms to encompass epistemological alternatives that confront the hegemonic and rational view of modern/colonial or Global North thinking. Regarding organization, this dissertation has two parts. In part I, I discuss decolonial movements in the research construction: 1) problematization of research methodology norms and 2) escreviver as research. In part II, I discuss the decolonial movements in the experiences of the English language practicum: 3) unveiling of epistemic silences; 4) physical and ontoepistemological movements; and 5) corazonar. This writing-living account of an English language practicum suggests that the decolonial movements we sought to build have imprinted other(ed) meanings on practicum and teacher education. These new meanings stress the need to build more circular relationships with agents of public basic education schools – point of departure and arrival of our teacher education programs.